Radiolabeling of protected tryptophan with [18F]fluoromethyl tosylate: Formation of [18F]fluoromethyl ester of tryptophan instead of 1-N-[18F]fluoromethyl tryptophan methylester. (October 2019) - Venkatachalam, T.K.; Stimson, D.H.R.; Frisch, K.; Pierens, G.K.; Bhalla, R.; Reutens, D.C.
Abstract: The reaction of [ 18 F]fluoromethyl tosylate with methyl(tert-butoxycarbonyl)-l -tryptophanate results in formation the O-alkylated ester of the tryptophan instead of alkylation of the indole nitrogen of tryptophan as initially anticipated. Treatment of protected tryptophan with NaH in dimethyl formamide (DMF) along with [ 18 F]fluoromethyl tosylate at 130°C results in the formation of [ 18 F]fluoromethyl(tert-butoxycarbonyl)-l -tryptophanate. Preferential formation of the O-alkylated product is postulated to be due to the hydrolysis of the ester. Confirmation of the O-alkylation was obtained by synthesizing the [ 19 F]fluoromethyl(tert-butoxycarbonyl)-l -tryptophanate insitu and examining its NMR characteristics using multiple NMR techniques. Similar results were also obtained when reacting Boc-tryptophan-N-carboxyanhydride precursor with fluoromethyl tosylate.